A Generalized Finite Element Method for Hydrodynamic Modeling of Short-channel Devices. Issue 1 (2001) - Shen, Min; Cheng, Ming-C.; Liou, J. J.
Abstract : A finite element method based on the least-squares scheme is developed for hydrodynamic simulation of two-dimensional short-channel semiconductor devices. Although this general-purpose finite element method has been shown in fluid dynamics to be more universal to flow problems than other finite element approaches and has been applied in recent years to a wide range of problems in fluid dynamics, it is still unfamiliar to the semiconductor device community. Application of the developed hydrodynamic least squares finite element method (LSFEM) to simulation of a 2D MESFET with a deep-submicron gate has demonstrated its robustness and effectiveness for the hydrodynamic device simulation.